Facts and memories of an Ukrainian landscape - Mageroski, Solange Franciele; Brumes, Karla Rosário (Sociedade & Natureza, 2019)
The landscape of Prudentópolis-PR got peculiar characteristics from the arrival of Ukrainian immigrants in the late nineteenth and early twentieth centuries. These individuals have contributed to a dynamic transformation of the local landscape, and the cultural attributes printed on the landscape make Prudentopolis be known as “the Brazilian Ukraine”. Therefore, the present article exhibit the landscape, through news contained in a newspaper. The Prácia Newspaper present in the Ukrainian community since the year 1912 is a relevant instrument for the understanding of these individuals in their new territory. In this article, we emphasize the materiality of culture, in other words, the elements visible in the landscape, since there are many material and immaterial elements.